2017
DOI: 10.1590/18069657rbcs20160203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral Nitrogen on Transfer of 13C-Carbon from Eucalyptus Harvest Residue Components to Soil Organic Matter Fractions

Abstract: ABSTRACT:The amount of harvest residues retained in Eucalyptus plantations strongly influences soil organic matter (SOM), but the efficiency of conversion to SOM may vary according to the type of residue. This study evaluated the recovery of C from Eucalyptus residue components -leaves, bark, branches, roots, and a mix of all residues -in different SOM fractions with or without mineral-N supplementation (200 mg kg -1 of N). Variation in natural 13 C abundance was used to trace the destination of residue-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As hypothesized, the input of C was inversely proportional to the removal of harvest residues, resulting in the AR exceeding the NRs by 3.0 Mg ha −1 year −1 . These results closely resembled the ones obtained by Demolinari et al [17]. The authors emphasized the significance of retaining the eucalyptus harvest residues in the field for the maintenance of soil C, particularly the bark, as it constitutes the most abundant component of harvest residues.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As hypothesized, the input of C was inversely proportional to the removal of harvest residues, resulting in the AR exceeding the NRs by 3.0 Mg ha −1 year −1 . These results closely resembled the ones obtained by Demolinari et al [17]. The authors emphasized the significance of retaining the eucalyptus harvest residues in the field for the maintenance of soil C, particularly the bark, as it constitutes the most abundant component of harvest residues.…”
Section: Discussionsupporting
confidence: 88%
“…In this sense, possibly, the quality of the eucalyptus harvesting residues contributing to the soil in the present study favors a higher humification coefficient due to the lower lability of the material, given the presence of recalcitrant components, like bark and branch, with an elevated C/N ratio (Table 2). Maintaining these residues on the soil surface has resulted in a higher C transfer from these components to the soil [17]. In addition, studies have shown that roots have a humification coefficient 2.3 times higher than surface-contributed residues due to the higher C/N ratio [57].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations